Analysis of antioxidant compounds and antioxidant activities from three materials of Lonicera. Issue 5 (February 2019) - Cai, Guojing; Deng, Qunxian; Li, Dongmei; Wang, Lamei; Sun, Yaqian
Abstract: The buds and leaves of 3 varieties (lines) of Lonicera were used as the materials to measure the contents of total phenols, flavone, anthocyanin, luteoloside and chlorogenic acid, at the same time, to analysis and compare the capacity of flower buds of scavenging DPPH, O2· −, ·OH to the leaves. The results showed that the contents of total phenolics in the leaves of 3 varieties (lines) were the highest, and the content of anthocyanins was the lowest. The content of total phenols, flavone, anthocyanin, luteoloside in leaves were higher than that of in flower buds; The capacity of flower buds and leaves of scavenging DPPH and O2 · − was higher than the capacity of scavenging ·OH. "Cuilei 109" buds and leaves had the highest antioxidant compounds and antioxidant activities.